Refinery Wastewater Treatment by a Novel Three-Dimensional Electrocoagulation System Design - Theydan, S. K.; Mohammed, W. T. (Engineering, Technology & Applied Science Research, 2022)
A novel three-dimensional electrocoagulation method was used in the current work to explore the treatment of refinery wastewater. Metal-Impregnated Granular Activated Carbon (MIGAC) was employed as a third particle electrode in the inventive design. A comprehensive investigation has been conducted to evaluate its performance. BET-specific surface area, total pore volume, X-ray Fluorescence (XRF), Energy-Dispersive X-ray spectroscopy (EDS), and Scanning Electron Microscopy (SEM) were employed for the characterization of MIGAC particle electrodes at pH=7, 30V applied voltage, 10g of particle electrodes, 175mL/min flow rate, and a supporting electrolyte (0.063M NaCl + 0.025M Na2SO4). The findings indicate that the effectiveness of Chemical Oxygen Demand (COD) elimination increased quickly after 20min to 66.93, 69.88, 77.59, 74.14, 81.26, 79.87, and 87.14% for Conventional Electrocoagulation (CEC). Three-dimensional electrocoagulation with granular activated carbon (TEC-RGAC), TEC-MIGAC (Al), TEC-MIGAC (Fe), and TEC-MIGAC (Al:Fe) with molar ratios of (1:1), (1:2), and (2:1) respectively were utilized. While turbidity removals were 99.04, 98.87, 99.23, 94.89, 92.42, 98.85, and 99.21% for CEC ,TEC-RGAC, TEC-MIGAC(Al), TEC-MIGAC(Fe), TEC-MIGAC(1:1), TEC-MIGAC(1:2), and TEC-MIGAC(2:1) respectively. The results demonstrated that the metal impregnation of GAC is an interesting method for achieving effective turbidity and COD removal from refinery wastewater. In both batch and repeat recycling tests, MIGAC with a mixture of aluminum and iron oxides removed turbidity and COD more effectively and efficiently than RGAC.